Interleukin-1 is a Biological Marker in Heart Failure - A. M. Alieva; V. A. Kislyakov; K. V. Voronkova; E. V. Reznik; R. A. Arakelyan; M. N. Saryev; R. K. Valiev; A. M. Rakhaev; E. T. Hasanova; M. R. Kalova; I. G. Nikitin (Архивъ внутренней медицины)
Inflammation is a universal response of a living organism to various damaging factors and is aimed at restoring tissue integrity and minimizing cell death. Proinflammatory cytokines, in particular interleukins, are active participants in the inflammatory response. In patients with heart failure, inflammatory reactions lead to damage to cardiomyocytes, their apoptosis and activation of neurohumoral systems, which contribute to the initiation of myocardial hibernation and mechanisms of its remodeling. The purpose of this review is to consider IL-1 as a diagnostic and prognostic marker in heart failure, as well as the effect of treatment with a recombinant form of IL-1R on the course of the disease.